FACTORS INFLUENCING SKIN NECROSIS RESULTING FROM EXTRAVASATION INJURIES AND THE RAPEUTIC APPROACHES IN THE PEDIATRIC INPATIENT WARD (JANUARY-DECEMBER 2019) - Saputro, Iswinarno Doso; Budi, Agus Santoso; Noverta, Dhitta Aliefia (Jurnal Rekonstruksi dan Estetik, 2020)
Highlights: Skin necrotic injuries from extravasation were associated with age, the type of fluid/drug administered, and the location of the peripheral venous line, but not with gender. Autolytic debridement remains a prevalent and commonly used initial treatment approach for these injuries. Abstract: Introduction: Extravasation injury, a common complication of intravenous therapy in children, Interestingly, the complications arising from extravasation injuries could be more severe than the underlying medical conditions, sometimes even requiring amputation. The study aimed to identify the factors influencing the occurrence of skin necrosis due to extravasation injuries and to categorize the treatment approaches employed at Dr. Soetomo General Academic Hospital's pediatric facility in Surabaya from January to September 2019. Methods: This research takes a descriptive-analytic approach with a cross-sectional method. It involves examining data obtained from medical records. Specifically, the study focuses on the medical records of 44 pediatric patients who received treatment at Dr. Soetomo Hospital in Surabaya for skin necrosis resulting from extravasation injuries from January to December 2019. The analysis includes a retrospective review of patient information, looking at their characteristics, risk factors, the modalities used for wound care therapy, and the outcomes of their cases. Results: There were 44 cases of skin necrotic injury due to extravasation injury, with the largest percentage of neonates group (34%), male gender (66%), hypertonic fluids/drugs (73%), most regions of dorsum and wrist dextra (17%) and the most used therapeutic modality was autolytic debridement (45%). Conclusions: We found that the incidence of skin necrosis due to extravasation injury is influenced by factors such as the patient's age, the type of fluid or drug administered, and the location of the peripheral venous line. However, gender was not found to be a significant factor in the incidence of these injuries. Interestingly, the initial treatment approach that is still commonly employed is autolytic debridement.